Gender quotas and bank risk - Liao, Rose C. (2022)
We assess the effects of board gender quota laws using a sample of banks from 39 countries. We document an increase in both stand-alone and systemic risk post-quota among banks that did not meet the quota prereform; the effect is stronger for banks in countries with a smaller pool of women in finance and low gender equality. We find that the propagation of poor governance practices by overlapping female directors and deterioration in the information environment post quota are likely channels driving the results. The evidence is consistent with some banks “gaming” the reform by strategically appointing insiders, which weakens the board’s monitoring function. Our results have policy implications and suggest that supply-side factors are key determinants of the outcome of mandated quotas.